PENGARUH RETURN SAHAM, EARNINGS, DAN VOLUME PERDAGANGAN SAHAM TERHADAP BID ASK SPREAD SEBELUM DAN SESUDAH PENGUMUMAN LAPORAN KEUANGAN - Poppy Nurmayanti (PEKBIS, 2012)
This research was intended to study and to analyze the influence of stock price,earnings and stock trading volume on bid ask spread before and after thepublication of financial statements both in good and in bad news. This research wasalso intended to identify the differences between bid ask spread before and after thepublication of financial statements both in good and bad news. Researchingpopulation are manufacture companies which listed in Jakarta Stock Exchange in2001 to 2005. The sample gained by purposive sample technique. The resultsample are 39 companies which 16 companies publishing financial statements ingood news and 23 companies others publishing financial statements in bad news.The hypotesis was analyzed by using a paired sample t tet and multiple regressionanalysis.The result showed that stock return consistently had a significant effect on bid askspread after the publication of financial statements in bad news. Earnings had asignificant effect on bid ask spread before the publication of financial statements inboth good and bad news. Stock trading volume had a significant effect on bid askspread before and after the publication of financial statements in both good and badnews. The results also showed that there were no differences between bid askspread before and after the publication of financial statements in good and badnews.